The Long Slumbering Offspring of Adam: The Evangelical Approach to the Tsimshian - Usher, Jean (Anthropologica, 2022)
William Duncan, lay missionary of the Anglican Church Missionary Society, laid the groundwork for his famous Metlakatla mission during his four years among the Tsimshian at Fort Simpson, British Columbia, from 1858 to 1862. Following the methods established by the C.M.S. Duncan gained intimate knowledge of Tsimshian society and this, together with his readiness to compromise with elements of that society, is considered the main reason for his successful conversion of the first group of Tsimshian. The disorientation of the Indians after the gold rush was also a major reason for their willingness to accept the dual goals of Christianity and civilization which their Victorian missionary offered to them in the new Utopia of Metlakatla.